2017
DOI: 10.1016/j.nuclphysb.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation power equations for black holes

Abstract: We derive the Hawking radiation power equations for black holes in asymptotically flat, asymptotically Anti-de Sitter (AdS) and asymptotically de Sitter (dS) black holes, This is done by using the greybody factor for these black holes. We observe that the radiation power equation for asymptotically flat black holes, corresponding to greybody factor at low frequency, depends on both the Hawking temperature and the horizon radius. However, for the greybody factors at asymptotic frequency, it only depends on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The equation was derived assuming the screen is placed close to the horizon, but respecting the radial NEC does not allow this. This should not be a particularly big issue since, up to an order one pre-factor, the evaporation rate should go as dM/dt ∼ β −2[31]. Which is consistent with Pennington's results[17] as well as ours.…”
supporting
confidence: 92%
“…The equation was derived assuming the screen is placed close to the horizon, but respecting the radial NEC does not allow this. This should not be a particularly big issue since, up to an order one pre-factor, the evaporation rate should go as dM/dt ∼ β −2[31]. Which is consistent with Pennington's results[17] as well as ours.…”
supporting
confidence: 92%
“…Since, v<c, hence and so on (8) Hence, it is clear that the terms of higher power of v/c in equation (7) can be neglected and finally, we have…”
Section: Theoretical Discussionmentioning
confidence: 98%
“…Brajesh et al converted the Stephen-Boltzmann-Schwarzschild-Hawking radiation formula in terms of Chandrasekhar limit [M ch ] and calculated their values for different test black holes existing in XRBs and AGN [7]. Mistry et al gave a model for the Hawking radiation power for black holes in asymptotically flat, asymptotically Anti-de Sitter (AdS) and asymptotically de Sitter (dS) black holes which showed that at low frequency, this model for asymptotically flat black holes, corresponding to grey body factor depends on both the Hawking temperature as well as event horizon and also the same for both Schwarzschild AdS and Reissner-Nordström AdS solutions and only depends on the Hawking temperature at asymptotic frequency [8].…”
Section: Introductionmentioning
confidence: 99%
“…A blackbody that emits radiant energy and has same relative spectral energy distribution at the same temperature, the difference in the energy distributions in smaller amount, is called greybody factor. Mistry et al [49] have obtained the Hawking radiation power equations in the background of asymptotically flat, AdS and dS BHs in (d + 1) dimensions by using the greybody factors for these BHs.…”
Section: Kdsmentioning
confidence: 99%